Mexico : 2016 Article IV Consultation-Press Release; Staff Report; and Informational Annex. (IMF Staff Country Reports; Country Report ;, 2016)
This 2016 Article IV Consultation highlights that Mexico has navigated successfully a complex external environment, characterized by heightened global financial-market volatility. The economy continues to grow at a moderate pace, and inflation is close to the target. The flexible exchange rate is playing a central role in helping the economy adjust to external shocks. Macroeconomic policies remain focused on maintaining strong fundamentals. Continued implementation of the structural reforms agenda should help lift potential growth over the medium term. The economy is projected to grow by 2.1 percent in 2016.